Multirotor Unmanned Aerial Vehicle Systems: An In-Depth Analysis of Hardware, Software, And Communication Systems - Çelebi, Yahya; Aydın, Hüseyin (My University, 2025)
This paper presents a comprehensive overview of multirotor unmanned aerial vehicle (UAV) systems, focusing on the mechanical integration of quadcopters. The rapid advancement and widespread adoption of UAVs have established them as a significant research and development field. This review examines the key components and technologies in UAV design and operation, including frame types, flight control boards, motors, electronic speed controllers, batteries, propellers, communication systems, and software. It analyzes various frame materials and configurations, detailing their advantages and limitations. The paper examines the essential role of flight control boards and inertial measurement units in maintaining stability and enabling autonomous flight. It explores motors, propellers, and power systems selection criteria and characteristics in detail. The review evaluates UAV communication technologies, including radio frequency, WIFI, Bluetooth, and infrared, comparing their capabilities and limitations. It also covers autopilot software and ground control stations for mission planning and execution. This comprehensive analysis serves as a valuable resource for researchers, engineers, and enthusiasts working with design, development, and application of multirotor UAV systems.
Keywords: UAV; Unmanned Aerial Vehicle; Quadcopter; Multirotor